Don't cry for us Argentinians: two decades of teaching medical humanities. Issue 2 (1st December 2000) - Acuña, Leopoldo E
Abstract : Medical humanities—history, literature, anthropology, ethics and fine arts applied to medicine—play an important role in medical education. For more than 20 years an effort has been made to obtain an academic identity for such a multidisciplinary approach. A distinction between humanitarianism and humanism is attempted here, the former being associated with medical care and the latter with medical education. In order more precisely to define the relationship between the arts and medicine, an alternative term "medical kalology", as-yet-unsanctioned, coined after the rules of medical terminology, is proposed. The Department of Medical Humanities in the School of Medicine, National University of La Plata, submits the following apologia: Don't cry for us Argentinians, since the teaching of medical humanities has helped our doctors to function more truly humanistically during the past two decades, and we intend to continue with this calling in the future.